Distribution and geochemical fractionation of lead in the continental shelf sediments around India. (9th May 2018) - Chakraborty, Sucharita; Chakraborty, Parthasarathi; Sarkar, Arindam; Kazip, Armoury; Mascarenhas‐Pereira, M.B.L.; Nagender Nath, B.
Abstract: This study provides the first, preliminary data on geochemical distribution and fractionation of Pb (a toxic heavy metal) in continental shelf sediments around India and identifies the factors that control geochemical fractionation processes of Pb in convoluted coastal marine sediments. For the sake of clarity, the long coastline (~7, 000 km) of India was divided into 6 coastal regions in this study. The total concentration of sedimentary Pb showed regional variation along the coast. The highest median concentration of Pb was found in the sediments collected from the north‐east region (26.5 mg/kg) followed by the north‐west (21.4 mg/kg) > central‐east (20.6 mg/kg) > south‐west (13.7 mg/kg) > south‐east (13.3 mg/kg) > central‐west (12.5 mg/kg) regions. Geochemical fractionation study suggested that the concentration of sedimentary Fe–Mn in oxyhydroxide form and the nature of sedimentary organic matters determined the geochemical distribution and fractionation of Pb in the shelf sediments. The major Pb hosting phases in the shelf sediments were the Fe–Mn oxyhydroxide phase followed by the sedimentary organic matter binding phases. The concentration of nonresidual Pb complexes in the shelf sediment was found to depend on the total sedimentary Pb loading. This study suggests that increase of anthropogenic Pb input and expansion of reduced oxygen levels in the coastal marine environment may have detrimental effects on the increasing mobility and bioavailability of Pb in the coastal areas around India.